Lista dos Pareceristas de 2018 - Régis Henrique dos Reis Silva; Luciana Cristina Salvatti Coutinho; Fabiana de Cássia Rodrigues; Mara Regina Martins Jacomeli (Revista Histedbr On-line, 2018)
Lista dos Pareceristas que colaboraram com a revista Revista Histedbr On-line no ano de 2018.